Feeding during neonatal therapeutic hypothermia, assessed using routinely collected National Neonatal Research Database data: a retrospective, UK population-based cohort study. (June 2021) - Gale, Chris; Longford, Nicholas T; Jeyakumaran, Dusha; Ougham, Kayleigh; Battersby, Cheryl; Ojha, Shalini; Dorling, Jon
Summary: Background: Therapeutic hypothermia is standard of care in high-income countries for babies born with signs of hypoxic ischaemic encephalopathy, but optimal feeding during treatment is uncertain and practice is variable. This study aimed to assess the association between feeding during therapeutic hypothermia and clinically important outcomes. Methods: We did a population-level retrospective cohort study using the UK National Neonatal Research Database. We included all babies admitted to National Health Service neonatal units in England, Scotland, and Wales between Jan 1, 2010, and Dec 31, 2017, who received therapeutic hypothermia for 72 h or died during this period. For analysis, we created matched groups using propensity scores and compared outcomes in babies who were fed versus unfed enterally during therapeutic hypothermia. The primary outcome was severe necrotising enterocolitis, either confirmed at surgery or causing death. Secondary outcomes include pragmatically defined necrotising enterocolitis (a recorded diagnosis of necrotising enterocolitis in babies who received at least 5 consecutive days of antibiotics while also nil by mouth during their neonatal unit stay), late-onset infection (pragmatically defined as 5 consecutive days of antibiotic treatment commencing after day 3), survival to discharge, measures of breastmilk feeding, and length of stay in neonatal unit. Findings: 6030 babies received therapeutic hypothermia, of whom 1873 (31·1%) were fed during treatment. Seven (0·1%) babies were diagnosed with severe necrotising enterocolitis and the number was too small for further analyses. We selected 3236 (53·7%) babies for the matched feeding analysis (1618 pairs), achieving a good balance for all recorded background variables. Pragmatically defined necrotising enterocolitis was rare in both groups (incidence 0·5%, 95% CI 0·2–0·9] in the fed group vs 1·1% [0·7–1·4] in the unfed group). The enterally fed group had fewer pragmatically defined late-onset infections (difference −11·6% [95% CI −14·0 to −9·3]; p<0·0001), higher survival to discharge (5·2% [3·9–6·6]; p<0·0001), higher proportion of breastfeeding at discharge (8·0% [5·1–10·8]; p<0·0001), and shorter neonatal unit stays (−2·2 [–3·0 to −1·2] days; p<0·0001) compared with the unfed group. Interpretation: Necrotising enterocolitis is rare in babies receiving therapeutic hypothermia. Enteral feeding during hypothermia is safe and associated with beneficial outcomes compared with not feeding, although residual confounding could not be completely ruled out. Our findings support starting milk feeds during therapeutic hypothermia. Funding: UK National Institute for Health Research Health Technology Assessment programme 16/79/13.